A comprehensive functional investigation of the human translocator protein 18 kDa (TSPO) in a novel human neuronal cell knockout model - Bader, Stefanie; Jahner, Tatjana; Dörfelt, Anett; Melchner, Doris; Cardon, Iseline; Siegmund, Heiko I.; Brochhausen, Christoph; Rupprecht, Rainer; Milenkovic, Vladimir M.; Wetzel, Christian H. (International journal of molecular sciences, 2024)
The translocator protein 18 kDa (TSPO) is a multifunctional outer mitochondrial membrane protein associated with various aspects of mitochondrial physiology and multiple roles in health and disease. Here, we aimed to analyse the role of TSPO in the regulation of mitochondrial and cellular functions in a human neuronal cell model. We used the CRISPR/Cas9 technology and generated TSPO knockout (KO) and control (CTRL) variants of human-induced pluripotent stem cells (hiPSCs). In a multimodal phenotyping approach, we investigated cellular and mitochondrial functions in neural progenitor cells (NPCs), astrocytes, and neurons differentiated from hiPSC CTRL and TSPO KO cell lines. Our analysis revealed reduced mitochondrial respiration and glycolysis, altered Ca2+ levels in the cytosol and mitochondrial matrix, a depolarised MMP, and increased levels of reactive oxygen species, as well as a reduced cell size. Notably, TSPO deficiency was accompanied by reduced expression of the voltage-dependent anion channel (VDAC). We also observed a reduced TSPO and VDAC expression in cells derived from patients suffering from major depressive disorder (MDD). Considering the modulatory function of TSPO and the similar functional phenotype of cells derived from patients with depression, we discuss a role of TSPO in the etiology or pathology of MDD. In summary, our findings indicate a general impairment of mitochondrial function in TSPO knockout (KO) cells. This deepens our insight into the intricate role of TSPO in a range of physiological and pathological processes.
Gesehen am 07.03.2025